Case Report: Femoral Neck Fracture in the Elderly - Aisya Nanda Bachtiar; Erlin Syahril; Erick Gamaliel Amba (Journal La Medihealtico, 2025)
A fracture, commonly referred to as a broken bone, is a complete or partial disruption of bone continuity, which may involve the articular cartilage and epiphyseal cartilage. In the elderly population, fractures most often result from a combination of falls and decreased bone density. This case report discusses a 62-year-old male patient who presented to Cendrawasih Community Health Center with complaints of right hip pain for two days. The pain worsened with right leg movement and subsided with rest. The onset of pain occurred after the patient fell while walking at home, landing directly on his right hip. For the past decade, the patient had been dependent on a walking aid following a right-sided stroke. After the fall, he was unable to stand or walk due to severe pain. Owing to persistent pain, he was subsequently referred to the emergency department of Ibnu Sina Hospital for further management. The patient’s medical history revealed hypertension controlled with routine medication, diabetes mellitus treated with metformin three times daily at a dosage of 500 mg, and a history of SNH, for which he had been regularly consuming Aspilet 80 mg daily for the past ten years. A femoral neck fracture refers to a break occurring at the neck of the femur, just below the femoral head and within the hip joint capsule. It is among the most common types of hip fractures in older adults, typically caused by falls. Arthroplasty, either hemiarthroplasty or total hip replacement, is regarded as the treatment of choice for most elderly patients with displaced femoral neck fractures.